THE INFLUENCE OF SELF-REGULATION AND SELF-ESTEEM ON ACADEMIC PROCRASTINATION IN STUNDENTS CONDUCTING ONLINE LEARNING AT THE FACULY OF ECONOMICS, STATE UNIVERSITY OF JAKARTA - Rachmi, Nabilla Aulia; Munawaroh; Faslah, Roni (Faculty of Economics and Business, Universitas Negeri Jakarta, 2022)
This study aims to determine the effect of self-regulation and self- esteem on academic prokrastination of student of thr Faculty of Economic at the State University Of Jakarta. This research was conducted for 8 months starting from January 2021 to August 2021. The method used in this study is a survey method. The sampel used in this study found 142 respondents from students of the Faculty of Economic class 2019 at the State University of Jakarta. The data was collected through the distributor of questionnaires using a Likert scale. Based of the result of research conducted, it was found that the influence of self- regulation has a negative and significant effect on academic procrastination. Self-esteem has a negative and significant effect on academic procrastination.